Length based spawning potential ratio of indian scad (Decapterus russeli, Rupell, 1928) in the South China Sea. Issue 1 (April 2021) - Priatna, A; Boer, M; Kurnia, R; Yonvitner,
Abstract: Spawning Potential Ratio (SPR) could be used to investigate stock indicators in terms of data-limited fisheries assessment. This study was aimed to assess the Length-based SPR of Indian scad ( Decapterus russelli ) in South China Sea. The length-frequency data were collected from 2015 to 2019, with approximately 250 fish sampled monthly. Fish samples were obtained from the catch of purse seiner which landed at Pemangkat fishing port. LB-SPR model required length-frequency and life history parameters i.e growth and maturity. The parameters L∞ K, M, L50, and L95 were 23.92 cm, 0.60 year-1, 1.00, 15.80, and 22.00 respectively. The estimated LB-SPR from static life-history parameters was 41%, while the stochastic SPR about 22% with a wide confidence interval, due to uncertainty of L∞ and K. According to the LB-SPR model considering the uncertainty, the estimated stochastic SPR is more acceptable in the condition of poor data. Besides, the high fishing pressure (F/M>1) indicated that SPR was lower than the target reference point (40%). However, in terms of the length at first capture (SL50) was greater than a length at first maturity (L50), it should be a consideration to estimate the SPR. Therefore, SPR was determined by 20%-40% or stock status on fully-exploited.